(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Nitrofurantoin is a broad-spectrum antimicrobial agent commonly prescribed for the treatment of urinary tract infections; however, its clinical effectiveness is often limited by poor aqueous solubility and reduced bioavailability. The present study focuses on the formulation and evaluation of a nitrofurantoin-loaded polymeric nanosuspension as a novel drug delivery system to enhance its antimicrobial efficacy while ensuring biocompatibility. The nanosuspension was prepared using a suitable nanoprecipitation technique with a biocompatible polymer and stabilizer to obtain stable nanoparticles with improved physicochemical properties. The developed formulation was characterized for particle size, polydispersity index, zeta potential, drug entrapment efficiency, and in vitro drug release profile. The optimized nanosuspension exhibited nanosized particles with a narrow size distribution, satisfactory surface charge, high drug entrapment efficiency, and sustained drug release, indicating good stability and controlled drug delivery. The antimicrobial activity of the formulation was evaluated against selected Gram-positive and Gram-negative bacterial strains, and the results demonstrated enhanced antibacterial activity compared with the pure drug, which may be attributed to improved dissolution, increased surface area, and better interaction with bacterial cells. Cytotoxicity analysis using an in vitro cell viability assay revealed acceptable cell viability at the tested concentrations, confirming the safety and biocompatibility of the developed formulation. Overall, the nitrofurantoin-loaded polymeric nanosuspension demonstrated improved physicochemical characteristics, enhanced antimicrobial performance, and favorable cytotoxicity, highlighting its potential as an effective nanocarrier for antimicrobial drug delivery. These findings suggest that polymeric nanosuspension technology offers a promising strategy to improve the therapeutic efficacy of nitrofurantoin and supports further preclinical and clinical investigations for its potential pharmaceutical applications.